ANALISIS PEMBELAJARAN BERDIFERENSIASI BERBANTUAN MEDIA AUGMENTED REALITY TERHADAP HASIL BELAJAR SISWA INKLUSI SPECIFIC LEARNING DISORDER DI SDN KUTOWINANGUN 12 SALATIGA - Zahra Sabila, Lavia; Sukasih, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research discusses specific learning disorder students who experience obstacles in the implementation of learning in inclusive classes. The purpose of this study is to find out what kind of learning is appropriate in the inclusion class especially for specific learning disorder students and to find out how differentiated learning assisted by augmented reality media can improve the learning outcomes of specific learning disorder inclusion students. This research method is a qualitative case study. The sample of this research is 5th grade students of SDN Kutowinangun 12 Salatiga, which is devoted to specific learning disorder students totalling 3 children. Differentiated learning assisted by augmented reality media is implemented in IPAS subjects with material on the five senses. The data analysis technique uses the Miles and Huberman model. Based on the results of the research that has been conducted by researchers, the results show that differentiated learning can provide good learning services for inclusive classes. So that students who are indicated to experience symptoms of specific learning disorder can receive learning material even with the limitations experienced. In addition, the application of technology-based media such as augmented reality media is able to deepen students' understanding of sensory material through animated images of the sensory organs. Thus, the learning outcomes of students with specific learning disorder in IPAS subjects with sensory material can increase.